Primary radiation therapy in stage I/II indolent orbital lymphoma – a comprehensive retrospective recurrence and toxicity analysis. (22nd March 2022) - Eze, Chukwuka; Friedrich, Isabelle; Hadi, Indrawati; Schmidt‐Hegemann, Nina‐Sophie; Hartoyo, Sarah Nindya; Trauth, Richard; Reitz, Daniel; Manapov, Farkhad; Siefert, Axel; Dreyling, Martin; Belka, Claus; Li, Minglun
Abstract: Purpose or Objective: To provide a comprehensive recurrence and toxicity analysis of patients treated with radiotherapy alone for stage I/II (Ann‐Arbor classification) indolent orbital lymphoma. Material and Methods: We retrospectively reviewed the medical charts of 46 patients (and 51 orbits) treated at our centre with radiotherapy between 1995 and 2012 for biopsy‐proven stage I/IIE primary orbital lymphomas. We evaluated treatment response and performed a comprehensive toxicity analysis with correlation to delivered radiation dose. Results: At diagnosis, the median age was 63.5 years (range: 20–92). At initial diagnosis 43 and 3 patients had unilateral, synchronous bilateral involvement while there were 2 cases of contralateral metachronous failure. The predominant histological subtype was extranodal marginal zone lymphoma of mucosa‐associated lymphoid tissue in 42 (91.3%), follicular in 1 (2.2%), lymphoplasmacytic lymphoma in 1 (2.2%) and other indolent histology in 2 (4.3%) patients. Most lymphomas were located in the conjunctiva (18/35.3%) or eyelids (18/35.3%). Thirty‐eight (82.6%) patients presented with stage I while 8/46 (17.4%) with stage II disease. The median radiation dose was 39.6 Gy (range: 21.6–48.6 Gy) delivered in 1.8–2 Gy single fractions. At a median follow‐up of 83 months (range: 7–258 months), the complete remission rate was 98%. A local relapse was observed in 2/51 (3.9%) orbits and 4/46 (8.7%) patients had systemic relapse. The 5‐ and 10‐year PFS rates were 79.2% (95% CI: 73.0%–85.4%) and 67.6% (95% CI: 59.4%–75.8%); 5‐ and 10‐year OS was 83.6% (95% CI: 77.9%–89.3%) and 76.5% (95% CI: 69.4%–83.6%), respectively. In total, 66 acute toxicity events (all‐grade) were observed: 5/51 (9.8%) ≥G2 acute conjunctivitis, 2/51 (3.9%) cases of G2 acute keratitis, 1/51 (2%) cases of ≥G2 ophthalmagia and 12/51 (23.5%) cases of ≥G2 xerophthalmia. Furthermore, 45 chronic adverse events were observed in 34/51 (66.7%) irradiated orbits with 30 late adverse events attributed to cataract. Conclusion: Our analysis confirms the role of radiotherapy alone at lower doses in the treatment of indolent orbital lymphomas. Further research is required to assess the efficacy of ultra‐low‐dose radiotherapy and anti‐CD20 monoclonal antibodies to further mitigate long‐term sequelae.